The wealthy and the well-born how political elites affect faction formation. - Bedia, Laurice Amy C. (2010.)
This paper is a study on the roles of two types of political elites, the landed elites and the business elites, on the different stages of faction formation. Factions are formed because of the desire of politicians to win in elections. The stages of faction formation are the recruitment of members and the selection of candidates for elections, definition of faction activities, decision-making on local policies and ordinances and the management of resource flow for the survival of the faction. The ways the two types of elites affect faction formation differ since the resources available to them also vary. Through interviews with sixteen political elites, eight of which were landed elites and eight were business elites, the study was able to determine the ways in which political elites affect faction formation. Landed elites affect faction formation by influencing the recruitment of members and decision-making of local ordinances through their financial contributions, experience, and political support from relatives in politics and business partners. Business elites on the other hand affect faction formation through providing significant financial contributions for faction activities and recruitment of members. The diversity of the resources of landed elites enables them to have greater effect over faction formation.
Research Project (Undergraduate, Bachelor of Arts in Political Science) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Political elites